Design of metasurface beam splitter based on polarization characteristics of incident wave. Issue 3 (11th February 2022) - Hao, Honggang; Tang, Yihao; Zheng, Sen; Ran, Xuehong
Abstract : A transmissive metasurface polarization beam splitter (MPBS) with three-layer dielectric substrate was designed to meet the application requirements of polarization beam splitting devices. The microstructure unit cell was composed of an elliptical patch and a square resonant ring, and the phase and amplitude responses to the x - and y -polarized incident waves were independent. Here 16 transmissive unit cells designed with a 90° phase difference and more than 0.8 transmission coefficient could be used to realize different functions by pre-designing distribution of "00", "01", "10", "11" encoding particles in x - and y -direction. We experimentally demonstrated a 2-bit encoding MPBS that separated x - and y -polarization incident waves into two different directions at 15 GHz respectively using specially designed encoding unit cells. The work may alleviate the shortage of advanced multifunctional devices and provide important application prospect in imaging, MIMO system, etc.